Experience of varied presentation of chronic progressive disseminated histoplasmosis in immunocompetent patients: A diagnostic conundrum - Roumi Ghosh; Pranshu Mishra; Sumit Sen; Prasanta Kumar Maiti; Govinda Chatterjee (Indian Journal of Dermatology, 2016)
We report two cases of chronic progressive disseminated histoplasmosis with unusual and rare clinical picture in a patient with no underlying risk factor. One 50-year-old male, presented with hoarseness of voice, chronic cough, with a history of nonresponding anti-tubercular therapy, revealed mucocutaneous lesions on examination. Fungating vocal cord lesions were visualized on bronchoscopy, raised suspicion of carcinoma. The second case, a 22-year-old female, referred to hospital with suspected vasculitis, with complaints of “off and on” fever with decreased oral intake, arthralgia, who later developed generalized nodular skin eruptions. On investigation, human immunodeficiency virus test was found to be negative in both the cases. Histopathological findings of skin biopsy, adrenal and bone marrow aspirates raised suspicion, whereas fungal cultures confirmed Histoplasma infection. Although diagnosis was delayed, but both of them were successfully treated with amphotericin B.